The Duverger-Demsetz Perspective on Electoral Competitiveness and Fragmentation: With Application to the Canadian Parliamentary System, 1867-2011 - J Stephen Ferris; Stanley L. Winer; Bernard Grofman (Center for Economic Studies and ifo Institute (CESifo), 2016)
We combine Duverger's Law (1954) with Demsetz's (1968) theory of natural monopoly to provide a novel perspective on electoral competitiveness in a single member district, plurality rule system. In the framework we develop, competitiveness depends on the contestability of elections, which declines as party fragmentation exceeds the long run level predicted by Duverger's Law. We provide support for this Duverger-Demsetz perspective by studying the relationship between the concentration of vote shares and a new index of electoral contestability over the history of the Canadian parliamentary system from 1867. Extension of the argument to proportional electoral systems is also considered.
Keywords: D70; D40; 330; electoral competition; economic competition; contestability; volatility adjusted vote margin; safe seats; marginal seats; Duverger; Demsetz